Pengelolaan Database dalam Meningkatkan Mutu Layanan Pondok Pesantren pada Seksi PD-Pontren Kantor Kementerian Agama Kabupaten Tuban - Maya Eldiany; Riza Amalia Nur Sholeha; Siti Niswatin; Muhammad Nuril Huda; Khoirul Fata; Sulikan (Program Studi Manajemen Pendidikan Islam, 2025)
The development of technology and information in the era of globalization has had a significant influence. This does not rule out the possibility in managing an insititution’s database. Database management in one quite important way of operating an organization’s information. The aim of this research is to determine database management in improving the quality of islamic boarding school services in the PD-Pontren section of the Tuban Regency Ministry of Religion Office. This research uses qualitative methods by conducting direct interviews with informants. The research results show that database management in the qualityy of islamic boarding school services is contained in the SINTREN and EMIS applications. This SINTREN aplication contains information about submitting new registration certificates, job extensions, and activation. Meanwhile the EMIS aplication puts more emphasis on the management of the islamic boarding school itself, starting from data on institutions, students, educators, and so on. Apart from system based manajement. This management is carried out directly at the Tuban Regency Ministry of Religion office and runs quie smoothly, although it does not rule out the ossibility that there will still be several obstacles in the implementation process. Both system based and manual management.